Manfaat Pemeriksaan Biomarker B-Rapidly Accelerated Fibrosarcoma (BRAF) pada Pasien Preoperatif dengan Kanker Tiroid - Edvano Adam Herbudi; Fanny Indarto; Purnamawati (Jurnal MedScientiae, 2023)
Thyroid cancer is the most common cancer of the endocrine system. In the detection of thyroid cancer, the gold standard examination is using fine-needle aspiration (FNA), where the cytology results are used in 60% - 80% of cases. FNA examination performed preoperatively determine the initial management of thyroid cancer. However, the FNA technique is limited by insufficient samples in about 2% - 20% of cases and about 10% - 30% of FNA results are classified as indeterminate (ITN) in the Bethesda system. Therefore, molecular tests such as BRAF biomarker screening are expected to help improve the detection of cases in this category. Methods: A literature search conducted from 4 databases (PubMed, ProQuest, ScienceDirect, and Google Scholar) published in the last 10 years with the keywords "preoperative", "braf" or "braf kinases", and "thyroid cancer". Results: Ten studies with total of 11,239 specimens classified in Bethesda III - VI showed increased sensitivity of 34.8% - 96.62% in the combination of FNA and BRAF techniques. Conclusion: The combination of preoperative FNA and BRAF examination increase sensitivity and help in the initial management of thyroid cancer in ITN or Bethesda III and IV group thyroid nodules in the detection of malignancy in the thyroid.